GC-MS fragmentation patterns of sprayed endosulfan and its sulphate metabolite in samples of Theobroma cacao L from a field kinetic study. Issue 4 (August 2019) - Vaikosen, Edebi N; Gibson, Lorraine T; Davidson, Christine M; Olu-Owolabi, Bamidele I; Adebowale, Kayode; Ebeshi, Benjamin U; Diagboya, Paul NE
Most environmental analytical methods for the determination of organochlorine pesticides (OCPs) are multi-residual with other organic compounds co-extracted and co-eluted. This has been observed in GC spectra using classical detectors like electron-capture detector (ECD) even after appropriate clean-up. This limitation could be resolved by using GC-MS methods which are more specific and selective. Thus, a commercial-grade endosulfan treated Theobroma cacao plantation was sampled. Representative samples comprising leaves, stem bark and pulp were obtained between 0.5 h and 60 days after treatment. Samples were analyzed for residual parent endosulfan ( α- and β -isomers) as well as the metabolite endosulfan sulphate using an ion trap GC-MS. The retention times and chromatogram peaks obtained for various endosulfan were identified and compared with reference standards, and confirmed with National Institute of Standards and Technology library. Results showed that the molecular ion at m/z 407 was exhibited by α- and β- endosulfan, representing the parent molecular ion M + ([C9 H6 Cl6 SO3 ] + ) . The α -isomer was more thermally stable, hence exhibited more relative abundance. Other predominant peaks were 339, 307, 277, 265, 243, 241, 207, 195, 160, 159, 99 and 75 m/z. The peak at m/z 159 was the base molecular ion. For endosulfan sulphate, the peak at m/z 422 corresponded to parent molecular ion (M + ), while m/z 424 was due to isotopic pattern characteristic of the chlorine atom. The peaks at 387, 357, 289, 272, 229, 206, 170, and 120 m/z were characteristic for the sulphate metabolite. The m/z peak at 272 was the base molecular ion, while m/z 143 may be due to metabolite diol and lactone. These results showed that the various endosulfan species can be identified and confirmed simultaneously using a GC-MS.